Checklist of marine and freshwater halacarid mite genera and species (Halacaridae: Acari) with notes on synonyms, habitats, distribution and descriptions of the taxa - Bartsch, Ilse (Zootaxa, 2009)
At the end of 2007, the family Halacaridae, superfamily Halacaroidea, included 1118 valid species in 63 genera. The genera and the number of species (in parentheses) are: Acanthohalacarus (1), Acanthopalpus (2), Acarochelopodia (8), Acaromantis (11), Acarothrix (5), Actacarus (24), Agaue (42), Agauides (2), Agauopsis (85), Anomalohalacarus (19), Arenihalacarus (1), Arhodeoporus (31), Astacopsiphagus (1), Atelopsalis (7), Australacarus (5), Bathyhalacarus (12), Bradyagaue (17), Camactognathus (3), Caspihalacarus (1), Coloboceras (3), Colobocerasides (2), Copidognathides (3), Copidognathus (359), Corallihalacarus (1), Enterohalacarus (1), Halacarellus (47), Halacaroides (2), Halacaropsis (5), Halacarus (75), Halixodes (3), Hamohalacarus (1), Himejacarus (1), Isobactrus (26), Limnohalacarus (13), Lobohalacarus (6), Lohmannella (36), Metarhombognathus (2), Mictognathus (3), Parasoldanellonyx (3), Parhalixodes (2), Pelacarus (1), Peregrinacarus (2), Phacacarus (1), Porohalacarus (2), Porolohmannella (1), Rhombognathides (6), Rhombognathus (103), Ropohalacarus (1), Scaptognathides (11), Scaptognathus (30), Simognathus (45), Soldanellonyx (9), Spongihalacarus (1), Stygohalacarus (1), Thalassacarus (1), Thalassarachna (14), Thalassophthirius (1), Troglohalacarus (1), Tropihalacarus (2), Werthella (10), Werthelloides (1), Winlundia (2), and Xenohalacarus (1). More than 1000 species live in marine and brackish water and almost 60 species exclusively in fresh or oligohaline to mesohaline brackish water (< S18‰). The checklist presents names used for halacarid genera and species of the world, names recognized as valid, synonyms, nomina nuda, names of species inquirendae and species erroneously attributed to the family Halacaridae. All valid species are supplemented with distributional data, namely, biogeographical provinces, depth zones and habitats, and references of descriptions of genera and species.